Gramatical error analysis and error of vocabulary in writing speech with theme ‘Sumpah Pemuda’ class IX students in SMP Bekasi - Yogi Purnama (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
The purpose of this study is to analyze the grammatical error of the affixation process inthe text of speech with the theme Sumpah Pemuda of junior high school class IX Bekasi is on theuse of dominant perfiks calculation percentage of 30% on errors in the use of perfiks se-. ke-, di-,ber-, mem-, meng-, me-, per-,Grammatical error of affixation process in speech texts with the theme'Sumpah Pemuda’ of junior high school class IX Bekasi, ie the use of infix does not occur ascalculated in percentage 0%. Writing in the text of the speech with the theme ‘Sumpah Pemuda’ ofjunior high school class IX Bekasi, namely on the suffix an-.yang reached 3.33%. Based on thecalculation, the vocabulary error in writing the text of the speech with the theme ‘Sumpah Pemuda’of 216.6%. the errors that often arise in the writing of the text of the speech with the theme SumpahPemuda' is the unwillingness and effectiveness of the word on the speech writing with the themeSumpah Pemuda’.